Gynaecological Acute Abdomen - Muhammad Ateeq Shazia Jehan , (Journal of Rawalpindi Medical College, 2012)
Background: To determine the prevalence and management outcome in female patients presenting to general surgeon with acute abdomen due to gynecological causes. Methods: In this observational, descriptive study female patients presenting in emergency with acute abdomen were evaluated. Management either conservative or intervention was planned. Patients with acute abdomen that were diagnosed due to gynecological causes were included in the study. Results: Over a period of two years, a total of 449 female patients with acute abdomen, were managed. Seventy nine (17.59%) patients were diagnosed as acute abdomen secondary to gynecological causes. Most of the patients (59%) were of child bearing age. Pain in the right iliac fossa was the commonest presenting symptom (54.43%). Surgical exploration was required in 68.35% patients. Ruptured ovarian cyst and adnexal torsion was the most frequent peroperative diagnosis. Conclusion: Acute abdominal symptoms in females need a thorough work up due to varied presentations, diagnoses and management options